Sustainable management of riverine N2O emission baselines - Wang, Shuo; Zhi, Wei; Li, Shengjie; Lyu, Tao; Ji, Guodong (Oxford University Press (OUP), 2025)
The riverine N2O fluxes are assumed to linearly increase with nitrate loading. However, this linear relationship with a uniform EF5r is poorly constrained, which impedes the N2O estimation and mitigation. Our meta-analysis discovered a universal N2O emission baseline (EF5r = k/[NO3−], k = 0.02) for natural rivers. Anthropogenic impacts caused an overall increase in baselines and the emergence of hotspots, which constitute two typical patterns of anthropogenic sources. The k values of agricultural and urban rivers increased to 0.09 and 0.05, respectively, with 11% and 14% of points becoming N2O hotspots. Priority control of organic and NH4+ pollution could eliminate hotspots and reduce emissions by 51.6% and 63.7%, respectively. Further restoration of baseline emissions on nitrate removal is a long-term challenge considering population growth and declining unit benefits (ΔN-N2O/N-NO3−). The discovery of EF lines emphasized the importance of targeting hotspots and managing baseline emissions sustainably to balance social and environmental benefits.
Keywords: nitrous oxide; emission factor; hotspots; sustainable; greenhouse gases; 41 Environmental Sciences; 4104 Environmental Management